2019
DOI: 10.3892/mmr.2019.10811
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of circular RNA molecular regulatory networks in clear cell renal cell carcinoma

Abstract: Increasing evidence has indicated that circular (circ)RNAs participate in carcinogenesis; however, the specific regulatory mechanisms underlying the effects of circRNAs, microRNAs (miRNAs/miRs) and genes on the development of clear cell renal cell carcinoma (CCRCC) remain unclear. In the present study, RNA microarray data from CCRCC tissues and control samples were downloaded from the Gene Expression Omnibus and The Cancer Genome Atlas, in order to identify significantly dysregulated circRNAs, miRNAs and genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Many studies have demonstrated that circRNAs participate in the tumorigenesis of ccRCC [18][19][20]. However, to date, the functions of circRNAs in ccRCC remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that circRNAs participate in the tumorigenesis of ccRCC [18][19][20]. However, to date, the functions of circRNAs in ccRCC remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to find novel biomarkers for reducing mortality rates [22]. With the development of genomic analysis platform, more and more circRNA have been identified, several studies have proved that circRNA was closely associated with ccRCC [23,24]. In this study, we aimed to investigate the biological roles and mechanisms of circ-APBB1IP in ccRCC development.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Ma et al found that 542 circRNAs were aberrantly expressed in clear cell RCC (ccRCC) by using a circRNA microarray. Among these, 324 circRNAs were significantly downregulated, whereas 218 were upregulated in ccRCC tumors [83]. Using the Arraystar microarray to profile seven matched ccRCC samples, Franz et al detected a total of 13,261 circRNAs, of which 78 circRNAs were upregulated and 91 were downregulated more than two-fold [84].…”
Section: Circrna Profiles In Rccmentioning
confidence: 99%